Nine years old child with nephrotic syndrome: a case of biopsy proven lupus nephritis in tertiary level medical college hospital in Mymensingh, Bangladesh - Hasan, Mahmud Javed; Ray, Nitai Chandra; Quddus, ASM Ruhul (Community Based Medical Journal, 2018)
We observed a case of a 9 years old female patient who presented with nephrotic syndrome and impaired renal function diagnosed to have Systemic Lupus Erythematosus (SLE). Lupus nephritis (LN) is a common major organ manifestation of SLE and causes significantly increased morbidity and mortality. Thus, all patients with SLE should be regularly screened for LN. This patient presented with nephrotic syndrome, pleural effusion and pericardial effusion which depicts the multisystem effects of SLE. This patient was treated with Oral Mycophenolate Mofetilin combination with steroid as induction therapy and attained remission after a month of treatment. Systemic lupus erythematosus should be considered in patients with nephrotic syndrome and these patients should have renal biopsy to determine renal involvement. CBMJ 2018 January: Vol. 07 No. 01 P: 40-44